Anemia, micronutrient deficiency, and elevated biomarkers of inflammation among women and children in two districts in the Northern Region of Ghana: A pilot study - Seth Adu-Afarwuah; Sika M. Kumordzie; K. Ryan Wessells; Charles D. Arnold; Xiuping Tan; Ahmed Fuseini; Stephen A. Vosti; Marjorie J. Haskell; Emily R. Becher; Jennie N. Davis; Katherine P. Adams; Reina Engle-Stone (PLoS ONE, 2025)
Introduction Previous data had shown a high prevalence of anemia and various micronutrient deficiencies (MNDs) in the Tolon and Kumbungu districts. We aimed to reassess these outcomes among lactating women (LW), women of reproductive age (WRA), and preschool children (PSC) to inform the design of a MN-fortified bouillon cubes trial, including the choice of micronutrients and selection of study sites; among WRA and PSC, we aimed to identify factors associated with anemia, MND, and inflammation, and to examine anemia co-occurring with MND and inflammation. Methods In this cross-sectional study (Nov 2020–Jan 2021), we randomly selected 7 urban and 7 rural clusters per district from those accessible at the time, recruited participants through a random walk-based search, and collected and analyzed breastmilk (LW) and venous blood (WRA and PSC). Ferritin (WRA and PSC), and retinol, retinol-binding protein, and zinc (PSC only) were adjusted for inflammation. Binary outcomes were defined using accepted cut-offs. Data analyses involved descriptive statistics, generalized linear mixed models (identify factors), and Rao-Scott chi-squared test (examine co-occurrence). Results Approximately 240 each of LW (average age, 30 y), WRA (30 y), and PSC (41 months) participated. Among LW, 41% had low breastmilk B-12; 8% had low breastmilk retinol. Among WRA, anemia was 31%; prevalences of MNDs were: iron, 45%; zinc, 79%; vitamin A, 1%; B-12, 12%; and folate, 12%; with 15% elevated α1‐acid glycoprotein (AGP) or C-reactive protein (CRP). Among PSC, anemia was 36%; prevalences of MNDs were: iron, 57%; zinc, 67%; vitamin A, 19%; and B-12, 19%; with 39% elevated AGP or CRP. Improved source of drinking water was associated with lower odds of anemia, iron deficiency, and vitamin A deficiency in WRA; rural or Kumbungu residence was linked to higher odds of vitamin B-12 or vitamin A deficiency in PSC. Anemia co-occurred with iron deficiency and inflammation in WRA and PSC. Conclusion Anemia and MNDs were common in this setting, suggesting the need for targeted interventions.